D4.5 Material from 2nd workshop - Hadjimitsis, Diofantos G.; Lysandrou, Vasiliki; Agapiou, Athos; Lasaponara, Rosa; Masini, Nicola (My University, 2017)
The present deliverable summarizes the outcomes of the second ATHENA workshop and provides all related material, both prior its accomplishment (e.g. agenda) and material such as presentations and list of participants. The second workshop was entitled: “Remote Sensing for Cultural Heritage beyond Europe” and was organised by Prof. R. Lasaponara and Prof. N. Masini from the CNR in Cyprus.
Keywords: ATHENA project; Workshop; Remote sensing; Cultural heritage